ESG REPORTING IN THE REPUBLIC OF MOLDOVA: CHALLENGES AND OPPORTUNITIES IN ALIGNING WITH EUROPEAN AND INTERNATIONAL STANDARDS - Roman BAHNARU (Eastern European Journal of Regional Studies)
The article examines the level and challenges of ESG (Environmental, Social, Governance) reporting in the Republic of Moldova, in the context of alignment with European regulations and global sustainability trends. Non-financial and non-standard reporting is mandatory in the Republic of Moldova for public entities with more than 500 employees, while for all other companies the reporting is voluntary. Thus, more and more companies have started to adopt international ESG standards voluntarily, influenced by market trends and the need to remain competitive on international market. The article proposes to analyze companies in the Republic of Moldova in terms of compliance with ESG standards, identifying challenges and opportunities for aligning with existing regulations.The article highlights the benefits of adopting ESG practices for the business environment. The analysis refers to international reporting tools and standards, such as GRI and ESRS, and how they can help increase transparency and strengthen investor confidence. In the context of the article, in provides a unique perspective on the adaptation of ESG by the companies in the context of the circular economy and existing ESG reporting standards. To improve ESG adoption in the Republic of Moldova, the article recommends integrating reporting into business strategies, investing in education and aligning with international standards, which would facilitate access to new opportunities and contribute to the sustainable development of the local economy to be competitive at international level.